Artificial Intelligence Techniques in IoT Sensor Networks - Mohamed Elhoseny; K Shankar; Mohamed Abdel-Basset (Chapman & Hall/CRC Distributed Sensing and Intelligent Systems Series, 2021)
Artificial Intelligence Techniques in IoT Sensor Networks is a technical book which can be read by researchers, academicians, students and professionals interested in Artificial Intelligence (AI), Sensor Networks and Internet of Things (IoT). This book intends to develop a shared understanding of applications of AI techniques in the present and near term. The book maps the technical impacts of AI technologies, applications, and their implications on the design of solutions for sensor networks. This book introduces the researchers and aspiring academicians the subject of latest developments and trends in AI applications for sensor networks in a clear and well-organized manner. It is mainly useful for research scholars in sensor networks and AI techniques. In addition, professionals and practitioners' working on the design of real time applications for sensor networks may be benefited directly from this book. Moreover, graduate and master students of any departments related to AI, IoT and sensor networks can find this book fascinating for developing expert systems or real time applications. The book is written in a simple and easy language, discusses the concepts from fundamentals which relieve the requirement of earlier background of the field finds it readable. From this expectation and experience, we believe that every library will be interested to collect copies of this book.